“Bridging Faith and Knowledge through Wittgenstein’s On Certainty” - Bernard Bragas (Scientia, 2019)
This paper argues that faith and knowledge are not mutually exclusive spheres of inquiry, but overlapping in a sense that faith is a viaduct of knowledge. Ludwig Wittgenstein’s On Certainty is the major material in consideration to argue this case.